Oxygen adsorbent for high-temperature variable-pressure oxygen production as well as preparation method and application of oxygen adsorbent
The oxygen adsorbent powder is prepared by solid-phase synthesis method, and the dry pressure method is molded and calcined at high temperature, which solves the problems of insufficient oxygen adsorption amount and oxygen adsorption/desorption speed of oxygen adsorption material, and achieves the effects of high strength, large adsorption capacity and rapid oxygen adsorption/desorption, which is suitable for high-temperature pressure-transforming oxygen conversion technology.
Patent Information
- Application Number
- CN202311184890.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-14
- Publication Date
- 2025-03-14
AI Technical Summary
The prior art has problems in the fields of small and medium-sized oxygen production and portable oxygen production, and the oxygen adsorption/desorption speed of the oxygen adsorbent material is insufficient, and the mechanical strength of the oxygen adsorbent is not sufficient to withstand high-speed airflow erosion.
The oxygen adsorbent powder is prepared by solid-phase synthesis method, co-precipitation method or sol-gel method, and molded by dry pressure method, combined with high temperature calcining steps, oxygen adsorbents with high strength, large oxygen adsorption amount and fast oxygen adsorption/desorption speed are prepared.
It realizes high strength, large adsorption capacity and fast oxygen adsorption/desorption of oxygen adsorbents, and is suitable for high-temperature pressure-transforming oxygen generation technology, improving the efficiency of small and medium-sized oxygen generation and mobile portable oxygen generation.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of air separation, and specifically relates to an oxygen adsorbent with high strength, large adsorption capacity and fast oxygen adsorption / desorption rate, and a preparation method and application thereof. Background Art
[0002] As an important industrial gas, oxygen plays an important role in the fields of chemical industry, metallurgy, medical treatment, sewage treatment, etc. At present, the commercial preparation technologies of pure oxygen mainly include cryogenic distillation and pressure swing adsorption. Cryogenic distillation is to separate oxygen from the air by using the different boiling points of oxygen and nitrogen. It purifies the air to remove water, carbon dioxide and a small amount of impurities in the air, and then compresses and cools it into liquid air. Then, by using the different boiling points of oxygen and nitrogen, the liquid air is evaporated and condensed multiple times in the distillation tower to separate oxygen and nitrogen. This method can produce more than 99.6% high-purity oxygen. Pressure swing adsorption oxygen production is a separation technology that uses the different adsorption capacities of gases on adsorbents at different pressures to separate oxygen and nitrogen in the air. It uses the molecular sieve adsorbent to adsorb nitrogen when pressurized, and oxygen flows out of the adsorption tower as product gas to separate oxygen and nitrogen. When the molecular sieve adsorbs nitrogen to saturation, the pressure of the adsorption bed is reduced, and the nitrogen adsorbed by the molecular sieve can be desorbed, and the molecular sieve adsorbent is regenerated and reused. Although commercial oxygen production technology can produce oxygen with a purity of more than 99.6%, it still faces many technical difficulties in the fields of small and medium-scale oxygen production and mobile and portable oxygen production.
[0003] High-temperature pressure swing oxygen production is a competitive oxygen production technology in the field of small and medium-scale oxygen production and portable oxygen production. It uses oxygen adsorbent materials to adsorb oxygen during atmospheric pressure air purge and desorb it under vacuum conditions or inert gas purge conditions. Among them, the preparation of oxygen adsorbent materials is the key to the application of high-temperature pressure swing oxygen production technology. First, the oxygen adsorbent needs to have a high oxygen adsorption capacity and a faster oxygen adsorption / desorption rate. Secondly, the oxygen adsorbent needs to have a high mechanical strength to withstand high-speed airflow scouring.
[0004] Mixed conductor materials are a type of ceramic material that has both oxygen ion conductivity and electronic conductivity, and have a very high selective adsorption capacity for oxygen. There have been no reports on the preparation of mixed conductor materials into oxygen adsorbents for high-temperature pressure-changing oxygen absorption. Summary of the invention
[0005] The purpose of the present invention is to provide an oxygen adsorbent for high-temperature pressure-changing oxygen absorption, and a preparation method and application thereof. The oxygen adsorbent material prepared by this technical solution has the advantages of high strength, large oxygen adsorption capacity, and faster oxygen adsorption / desorption rate.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing an oxygen adsorbent for high-temperature pressure-variable oxygen production, comprising the following steps:
[0008] (1) Preparation of oxygen adsorbent powder: The oxygen adsorbent powder is prepared by solid phase synthesis, coprecipitation or sol-gel method;
[0009] (2) Preparation of mixed powder: The oxygen adsorbent powder obtained in step (1) is mixed with a solvent, a binder, and a lubricant in a certain proportion by stirring to obtain a mixed powder;
[0010] (3) Oxygen adsorbent molding: preparing and molding by dry pressing through a mold;
[0011] (4) High temperature calcination: raise the temperature to 400-800°C, keep it at this temperature for 0.5-10 hours to remove the organic additives, and then cool it down to room temperature to obtain the product.
[0012] Based on the above technical solution, further, in step (1), the metal element in the oxygen adsorbent powder is one or a combination of two or more of Ba, Sr, Co, Fe, La, Fe, Cu, and Ca.
[0013] Based on the above technical solution, further, the metal element composition of the oxygen adsorbent powder in step (1) is Ba 0.1-0.8 Sr 0.1-0.8 Co 0.5-1.0 Fe 0.1-0.4 O 3-δ 、LaFe 0.1-0.4 Cu 0.5-1.0 O 3-δ or SrCa 0.1-0.4 Fe 0.5-1.0 O 3-δ .
[0014] Based on the above technical scheme, further, the specific process of the solid phase synthesis method in step (1) is: weigh the raw materials of the oxygen adsorbent powder according to the stoichiometric ratio and place them in a ball mill, add water or ethanol and ball mill for 5-30 hours, dry the ground powder, crush it, sieve it to obtain the primary powder of the oxygen adsorbent, and then roast the primary powder at 800-1000°C for 1-10 hours to obtain the oxygen adsorbent powder.
[0015] Based on the above technical scheme, further, the specific process of the sol-gel method in step (1) is: weighing the nitrates of all metal ions according to the stoichiometric ratio, adding citric acid and EDTA, the molar ratio of citric acid: EDTA: total metal ions is 1-2:1-2:1, adjusting the pH value to 8-10, continuously heating and stirring until it becomes a sol state, calcining the colloid at 200-500°C to obtain a primary powder, and then calcining the primary powder at 800-1000°C for 1-10h to obtain an oxygen adsorbent powder.
[0016] Based on the above technical solution, further, the particle size of the oxygen adsorbent powder described in step (1) is 0.1mm-0.5mm.
[0017] Based on the above technical solution, further, in step (2), 0.5%-5% of the weight of the oxygen adsorbent powder by solvent, 0.5%-10% of the weight of the binder, and 1%-10% of the weight of the lubricant are added to the mixed powder; the solvent used is one of deionized water, methanol, ethanol, and acetone; the binder used is one of methyl cellulose, ethyl cellulose, gum arabic, soluble starch, polyvinyl alcohol, and dextrin, or a mixture of two or more thereof; the lubricant used is one of graphite, talc, stearate, silicone oil, and oleic acid, or a mixture of two or more thereof.
[0018] Based on the above technical solution, further, the specific process of step (3) is: putting the mixed powder prepared in step (2) into an extrusion mold, and obtaining the oxygen adsorbent by dry pressing through a single punch tablet press; the shape of the mold is cylindrical, annular, rectangular, or square.
[0019] Based on the above technical solution, further, the single punch tablet press has a dry pressing pressure of 1-10 MPa and a dry pressing time of 1-10 s.
[0020] Based on the above technical solution, further, in step (4), the heating rate is 0.5-1°C / min; the cooling rate is 1-3°C / min.
[0021] The present invention also provides an oxygen adsorbent prepared by the above preparation method.
[0022] The present invention also provides the use of the above oxygen adsorbent in high temperature pressure swing adsorption (PSA) or vacuum pressure swing adsorption (VPSA) oxygen production.
[0023] The oxygen adsorption prepared by the present invention has the following beneficial effects:
[0024] 1. The oxygen adsorbent material prepared by the present invention has the advantages of high strength and large adsorption capacity. Different from the commercial pressure swing adsorption oxygen production, the commercial molecular sieve adsorbent adsorbs nitrogen and oxygen is used as the product gas. The oxygen adsorbent material prepared by the present invention adsorbs oxygen. When the adsorbent adsorbs oxygen to saturation, the adsorption tower is evacuated, the oxygen adsorbed by the adsorbent can be desorbed, and the oxygen adsorbent material is regenerated and reused.
[0025] 2. The preparation method of the present invention has simple operation steps and high production efficiency, which is conducive to large-scale production of oxygen adsorbents. DETAILED DESCRIPTION
[0026] The present invention is further described below by examples. It is noted that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. Changes and substitutions made after understanding the content and method of the present invention should all be included in the protection scope of the present invention.
[0027] Example 1
[0028] A kind of Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3-δ (BSCF) The preparation method of oxygen adsorbent, the specific steps are as follows:
[0029] (1) Preparation of BSCF oxygen adsorbent powder: BaCO3, SrCO3, Co3O4, and Fe2O3 raw material powders were weighed according to the stoichiometric ratio and placed in a ball mill. The raw material powders were ball milled with water for 20 h. The ground powders were dried and crushed through a 100-mesh sieve to obtain BSCF oxygen adsorbent primary powders. The primary powders were then calcined at 1000°C for 3 h to obtain BSCF oxygen adsorbent powders.
[0030] (2) Preparation of mixed powder: BSCF powder, deionized water, methyl cellulose and graphite were mixed in a weight-to-mass ratio of 100:1:1:1, and mixed in a mixer to prepare a mixed powder;
[0031] (3) Oxygen adsorbent molding: The mixed powder in step (2) is placed in a cylindrical mold and pressed into a shape by a single punch tablet press, with a dry pressing pressure of 1 MPa and a dry pressing time of 3 seconds; the molded oxygen adsorbent is placed in a high-temperature muffle furnace for calcination, and the temperature is slowly increased to 400°C at a heating rate of 0.5°C / min, and the temperature is kept for 1 hour to remove the organic additives, and finally the temperature is lowered to room temperature at a rate of 2°C / min.
[0032] The prepared BSCF cylindrical oxygen adsorbent is 5mm long and 2mm in outer diameter. The strength of the BSCF oxygen adsorbent is determined to be 15Mpa by the three-point bending method. The BSCF oxygen adsorbent is subjected to a pressure swing adsorption oxygen production performance test. The pressure swing adsorption oxygen production system consists of two adsorption towers. The program control valve is switched under PLC control to complete the adsorption / desorption process, thereby completing continuous oxygen production. The oxygen adsorbent material adsorbs oxygen during the atmospheric pressure air purge process, and when the adsorption is saturated, it is desorbed under vacuum conditions. The oxygen is desorbed to achieve the reuse of the oxygen adsorbent material. The oxygen adsorption tower is filled with 350g BSCF oxygen adsorbent, the air intake volume is 20L / min, adsorption is carried out under atmospheric pressure air, the adsorption time is 70s, desorption is carried out under vacuum conditions, the desorption time is 60s, the vacuum degree is -0.098Mpa, and the test results show that the oxygen production capacity is 800mL / min and the oxygen purity is 99.5%.
[0033] Example 2
[0034] A LaFe 0.2 Cu 0.8 O 3-δ (LFC) The preparation method of oxygen adsorbent, the specific steps are as follows:
[0035] (1) Preparation of LFC oxygen adsorbent powder: La2O3, CuO, and Fe2O3 raw material powders were weighed according to the stoichiometric ratio and placed in a ball mill, and ball milled for 20 h using ethanol as the medium. The ground powders were dried and crushed through a 100-mesh sieve to obtain LFC oxygen adsorbent primary powders, and then the primary powders were calcined at 900°C for 3 h to obtain LFC oxygen adsorbent powders;
[0036] (2) Preparation of mixed powder: LFC powder, polyvinyl alcohol and oleic acid were mixed in a weight-to-mass ratio of 50:1:1, and mixed in a mixer to prepare a mixed powder;
[0037] (3) Oxygen adsorbent molding: The mixture powder in step (2) is placed in a circular mold and pressed into shape by a single punch tablet press, with a dry pressing pressure of 6 MPa and a dry pressing time of 3 seconds; the molded oxygen adsorbent is placed in a high-temperature muffle furnace for calcination, and the temperature is slowly increased to 800°C at a heating rate of 0.5°C / min, and the temperature is kept for 1 hour to remove the organic additives, and finally the temperature is lowered to room temperature at a rate of 2°C / min.
[0038] The prepared LFC annular oxygen adsorbent has an outer diameter of 5 mm, an inner diameter of 2 mm, and a thickness of 2 mm. The strength of the LFC oxygen adsorbent is determined to be 15 MPa by a three-point bending method. The LFC oxygen adsorbent is subjected to a performance test under the same conditions as in Example 1. The oxygen adsorption tower is filled with 500 g of LFC oxygen adsorbent, the air intake volume is 20 L / min, adsorption is carried out under normal pressure air, the adsorption time is 60 s, desorption is carried out under vacuum conditions, the desorption time is 50 s, the vacuum degree is -0.098 MPa, and the test results show that the oxygen production capacity is 600 mL / min and the oxygen purity is 99.5%.
[0039] Example 3
[0040] A SrCa 0.2 Fe 0.8 O 3-δ (SCF) The preparation method of oxygen adsorbent, the specific steps are as follows:
[0041] (1) Preparation of SCF oxygen adsorbent powder: All metal ions Ca 2+ , Sr 2+ , Fe 3+ Nitrate was weighed in a stoichiometric ratio and placed in a beaker, and citric acid and EDTA were added, with a molar ratio of citric acid: EDTA: total metal ions of 1.5:1:1. The pH value was adjusted to 8-10 with aqueous ammonia, and the solution turned into a transparent dark purple color. The solution was heated and stirred continuously until it was in a sol state, and the colloid was calcined at 400°C to obtain a primary powder, and then the primary powder was calcined at 950°C for 5h to obtain SCF oxygen adsorbent powder.
[0042] (2) Preparation of mixed powder: SCF powder, dextrin and graphite were mixed in a weight-to-mass ratio of 50:1:1, and mixed in a mixer to prepare a mixed powder;
[0043] (3) Oxygen adsorbent molding: The mixed powder in step (2) is placed in a circular mold and pressed into a shape by a single punch tablet press, with a dry pressing pressure of 6 MPa and a dry pressing time of 1 s; the molded oxygen adsorbent is placed in a high-temperature muffle furnace for calcination, and the temperature is slowly increased to 600°C at a heating rate of 1°C / min, and the temperature is kept for 1 hour to remove the organic additives, and finally the temperature is lowered to room temperature at a rate of 2°C / min.
[0044] The prepared SCF annular oxygen adsorbent has an outer diameter of 3mm, an inner diameter of 1mm, and a thickness of 2mm. The strength of the SCF oxygen adsorbent measured by the three-point bending method is 10Mpa. The SCF oxygen adsorbent is tested for performance under the same conditions as in Example 1. The oxygen adsorption tower is filled with 380g of SCF oxygen adsorbent, the air intake is 20L / min, adsorption is performed under normal pressure air, the adsorption time is 30s, desorption is performed under vacuum conditions, the desorption time is 20s, the vacuum degree is -0.098Mpa, and the test results show that the oxygen production capacity is 500mL / min and the oxygen purity is 99.5%.
Claims
1. A method for preparing an oxygen adsorbent for high temperature pressure change oxygen production, characterized in that: The following steps are involved: (1) Preparation of oxygen adsorbent powder: The oxygen adsorbent powder is prepared by solid phase synthesis, coprecipitation or sol-gel method; (2) Preparation of mixed powder: The oxygen adsorbent powder obtained in step (1) is mixed with a solvent, a binder, and a lubricant in a certain proportion by stirring to obtain a mixed powder; (3) Oxygen adsorbent molding: preparing and molding by dry pressing through a mold; (4) High temperature calcination: raise the temperature to 400-800°C, keep it at this temperature for 0.5-10 hours to remove the organic additives, and then cool it down to room temperature to obtain the product.
2. The preparation method according to claim 1, characterized in that: The specific process of the solid phase synthesis method in step (1) is as follows: weigh the raw materials of the oxygen adsorbent powder according to the stoichiometric ratio and place them in a ball mill, add water or ethanol and ball mill for 5-30 hours, dry the ground powder, crush it, sieve it to obtain the primary powder of the oxygen adsorbent, and then calcine the primary powder at 800-1000°C for 1-10 hours to obtain the oxygen adsorbent powder. The specific process of the sol-gel method is: weigh the nitrates of all metal ions according to the stoichiometric ratio, add citric acid and EDTA, the molar ratio of citric acid: EDTA: total metal ions is 1-2:1-2:1, adjust the pH value to 8-10, continue heating and stirring until it is in a sol state, calcine the colloid at 200-500°C to obtain a primary powder, and then calcine the primary powder at 800-1000°C for 1-10h to obtain an oxygen adsorbent powder.
3. The preparation method according to claim 1, characterized in that: The particle size of the oxygen adsorbent powder described in step (1) is 0.1 mm-0.5 mm.
4. The preparation method according to claim 1, characterized in that: In step (2), 0.5%-5% of the weight of the oxygen adsorbent powder is added to the mixed powder, and 0.5%-10% of the binder and 1%-10% of the lubricant are added; the solvent used is one of deionized water, methanol, ethanol, and acetone; the binder used is one of methyl cellulose, ethyl cellulose, gum arabic, soluble starch, polyvinyl alcohol, and dextrin, or a mixture of two or more thereof; the lubricant used is one of graphite, talc, stearate, silicone oil, and oleic acid, or a mixture of two or more thereof.
5. The preparation method according to claim 1, characterized in that: The specific process of step (3) is: putting the mixed powder prepared in step (2) into an extrusion mold, and dry pressing the oxygen adsorbent through a single punch tablet press; the shape of the mold is cylindrical, annular, rectangular, or square.
6. The preparation method according to claim 5, characterized in that: Dry pressing pressure 1-10Mpa, dry pressing time 1-10s.
7. The preparation method according to claim 1, characterized in that: In step (4), the heating rate is 0.5-1°C / min; the cooling rate is 1-3°C / min.
8. The oxygen adsorbent obtained by the preparation method according to any one of claims 1 to 8.
9. Use of the oxygen adsorbent according to claim 9 in high temperature pressure swing adsorption (PSA) or vacuum pressure swing adsorption (VPSA) oxygen production.
Citation Information
Patent Citations
Molecular sieve adsorbent for separating oxygen from air by means of pressure swing adsorption and preparation method thereof
CN101708456A
Oxygen adsorbent, preparation method and application thereof
CN101837278A
Oxygen adsorbent
CN106861602A
Oxygen producing method and apparatus by pressure swing method using high temperature oxygen adsorbent
JP2008012439A
Oxygen-producing method and oxygen-producing apparatus according to pressure swing adsorption method that employs oxygen-selective adsorbent
JP2010012367A